Burden of Obesity and Diabetes Mellitus in Low Income Area of Lahore. - Shehnaz Khan; Tahseen Kazmi; Muhammad Muneeb; Saira Farhat; Noor Shahid (University of Lahore, 2022)
Objective: To find prevalence of obesity, diabetes and pre-diabetes and its association with non-communicable diseases in a local community of Mughalpura, Lahore. Methodology: A cross-sectional study was conducted at Mughalpura Division, Lahore, Pakistan from January to June, 2021. The demographic details and data on blood sugar levels were collected from 380 participants using cluster sampling. Blood sugar ratio level was obtained as a key factor for observing diabetes and pre-diabetes. A test of association was used to observe the significant relation between diabetes with Basal Metabolic Index. Results: The average age of the participants was 46.0 + 12.6 SD (in years). Almost two-third of the participants were female and majority of participants were Punjabi. Among the total participants, 293 (77.1%) had normal blood sugar level, whereas 25 (6.6%) were pre-diabetic and 62 (16.3%) were diabetic. The under-weight participants were 10 (2.6%), 86 (22.6%) were normal, 143 (37.6%) were over-weight and 141 (37.1%) were obese. Conclusion: High prevalence of diabetes among obese individuals was found in a poor community of Mughalpura. Most of them were obese females. Significant association was found between systolic hypertension, diabetes and obesity.